The effect of elevated atmospheric ρco2 on phosphorus nutrition of white clover (Trifolium repens L.) - Almeida, José Pedro Pestana Fragoso de (1998)
White clover (Trifolium repens L.) and its symbiosis with Rhizobium are important components of temperate and mediterranean grassland ecosystems. From the factors affecting while clover growth and its symbiosis, the P nutrition is particularly important. The actual atmospheric carbon dioxide partial pressure (ρco2) of 35 Pa is predicted to double within the next century. This increase rnay result in increases of plant biomass dependent, however, from nutrient availability. Earlier studies showed that under nitrogen (N) and phosphorus (P) deficiency the ρco2 stimulation of plant growth was reduced. In contrast, under field conditions in the Swiss Free Air Carbon dioxide enrichment experiment, under a high P availability and a low N fertilisation, white clover had a positive yield response to elevated ρco2, associated with an increase of N derived from the symbiosis (Nsym). Therefore a question arises about the possible effect of P deficiency on the response of white clover and its symbiosis lo elevated ρco2. The reduction of leaf stomatal conductance under elevated ρco2 results in a decrease of leaf transpiration rate. Therefore, we expected that (1) this decrease of leaf transpiration would affect the transport flow of P from root to the shoot, changing the P partitioning. At the level of symbiosis, in contrast to earlier reports on P deficiency, investigations from other stress factors concluded that the C supply from the shoot to the nodules did not regulate nodule N2 fixation. Alternatively the plant N demand was suggested to be the regulatory factor for the Nsym. Therefore we expected that (2) the decline of N2 fixation under P deficiency would result from an adaptation to a lower white clover N demand, irrespective of the C availability from the shoot. To test these two hypotheses a study was undertaken with white clover under controlled environment on quartz sand as growth substrate with a low N (1.5 mM N) nutrient solution. In a first experiment, two atmospheric ρco2 (35 and 70 Pa) were combined with four levels of P supply (0.0027; 0.075; 0.67 and 2 mM) aiming to assess the physiological processes at the whole plant level. A second experiment was conducted in a similar system to assess the combined effects of two atmospheric ρco2 (35 and 70 Pa) and two levels of P supply (0.0027 and 0.075 mM) on nodulation of white clover. Our results showed that the response of white clover to P nutrition and elevated ρco2 consists of several mechanisms. At low P, the low rates of leaf transpiration led to low rates of shoot P uptake per plant, irrespective of ρco2. The higher leaf photosynthetic rates (measured on the young leaves) under elevated ρco2 appeared to be enabled by an increase of the Pi remobilization from leaf structural P fraction and from an increased senescence of old leaves. With increasing P supply, the estimated shoot P uptake rate per plant increased; however, it was reduced in parallel to a reduced transpiration rate under elevated as compared lo ambient ρco2. This ρco2-induced decline of shoot P uptake was associated with an absolute change of P partitioning in favour to the root, while the total P content per plant was not affected by ρco2. The increased P content of roots resulted in a marked reduction of root acid phosphatase activity under elevated ρco2. Elevated ρco2 did not affect nodulation, nodule growth and percentage N from symbiosis (%Nsym). P deficiency prevented nodulation or stopped nodule growth when applied to modulated plants and strongly reduced plant growth. Even though N2 fixation was clearly reduced under P deficiency these plants were not N limited since N concentration was significantly higher as compared with the other P levels. The combined N supply (mineral and symbiotic) covered the low demand of these P deficient plants. With increasing P supply nodule growth and %Nsym increased. The lack of an effect of the increased rate of photosynthesis on N2 fixation under elevated ρco2 and the high WSC contents in roots and nodules indicated that C supply did not limit the N2 fixation, irrespective of P supply. Alternatively, a systemic effect appeared to be involved in the response of the N2 fixation process, most likely triggered by white clover N demand. The balance between N demand and N fixation was attained by a partial compensation of nodule function (specific N2 fixation) to nodule mass. Apparently, this balance would not change under elevated ρco2 since nodule growth and Nsym were not affected by ρco2. However, the N efficiency was higher under elevated ρco2 (higher plant dry mass at lower N concentration), most likely due to a different N allocation within the plant (between sinks). Questions arising from these results are discussed in view of developing further investigations.